Can the Hyperaccumulating Plant Arabidopsis halleri in Feed Influence a Given Consumer Organism (Rattus norvegicus var. alba)? - Válek, Petr; Sloup, Vladislav; Jankovská, Ivana; Langrová, Iva; Száková, Jiřina; Miholová, Daniela; Horáková, Barbora; Křivská, Daniela (Bulletin of environmental contamination and toxicology, 2015)
Zinc and cadmium concentrations in rat (Rattus norvegicus var. alba) tissues were analyzed by inductively coupled plasma optical emission spectrometry. Rats were fed the zinc and cadmium hyperaccumulating plant, Arabidopsis halleri. When compared to the control group, a Cd increase in all tissues (liver, kidneys, small intestine, spleen, testes, muscle), with the exception of bone tissue was observed. In comparison to the control group, the kidneys, liver and small intestine contained 375, 162, and 80 times more Cd, respectively. Differences between zinc concentrations in rats fed with A. halleri and those of the control group were significant only in the small intestine and kidney tissues. Results suggest using the hyperaccumulating plant A. halleri as a feed stresses the consumer organism not through its Zn content, but through its Cd content.
Keywords: Liver; Rats; játra; Zinc; Trace Elements; Intestine, Small; krmivo pro zvířata; Rats, Wistar; mužské pohlaví; Arabidopsis Proteins; tenké střevo; testis; Muscles; krysa rodu Rattus; proteiny huseníčku; slezina; Optics and Photonics; spektrální analýza; Cadmium; Arabidopsis; zvířata; Temperature; svaly; optika a fotonika; ledviny; kadmium; Animal Feed; zinek; Spectrum Analysis; potkani Wistar; Kidney; stopové prvky; Spleen; Testis; teplota; Male; Animals